(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
Background: Fever of unknown origin remains one of the most difficult challenges in the clinical medicine, and it needs long series of diagnostic investigations and tests. Blood smear and bone marrow aspiration are diagnostic tools in evaluating patients with unexplained fever Objective: The role of peripheral blood smear and bone marrow aspiration in early causative diagnosis for fever of unknown origin . Methods: This is a prospective descriptive study conducted in Tishreen University Hospital in Lattakia, Syria, over a period of one year ( 2017-2018 ). It has shown the experience of the haematology department in approaching the patients with fever of unknown origin. Blood smear was performed in every patient , and bone marrow aspiration had been done when blood smear was undiagnosed. Bone marrow biopsy had been done if it was necessary and to complete the haematological study. The diagnostic yields of these procedures in fever of unknown origin patients were determined. Results: A total of 87 patients with classical fever of unknown origin were involved in the study, a definitive diagnosis could be achieved in 67(77%) patients, and 24 ( 27.6% ) patients with infective aetiology had been found to be the most common cause of fever of unknown origin. The diagnostic yields of peripheral blood smear and bone marrow aspiration were 16% and 31% respectively. The bone marrow biopsy was useful in 11 (13%) patients. A specific diagnosis without haematological study could be achieved in 15(17%) patients, and increased to 64 % with cytohaematological study and to 77% with complete haematological study ( with bone marrow biopsy) . Conclusion: Peripheral blood smear and bone marrow examination had been shown good diagnostic yields in evaluating patients with fever of unknown origin for achieving a specific diagnosis or a diagnostic key of other diagnosis. مقدمة: تبقى الحمى مجهولة السبب من أكثر التحديات صعوبة في الطب السريري، فهي تتطلب سلسلة طويلة من الإستقصاءات والاختبارات التشخيصية، وتعد اللطاخة الدموية المحيطية و بزل نقي العظم من الوسائل الاستقصائية المدرجة في تقييم مرضى الترفع الحروري غير المفسر. هدف البحث: أهمية اللطاخة الدموية المحيطية و بزل نقي العظم في التشخيص السببي المبكر للحمى مجهولة السبب التقليدية. الطرائق: دراسة مستقبلية وصفية تم إجراؤها في مستشفى تشرين الجامعي في اللاذقية خلال عام واحد (2017-2018) أظهرت تجربة شعبة أمراض الدم في مقاربة مرضى الحمى مجهولة السبب التقليدية. تم إجراء لطاخة دموية محيطية لكل مرضى الترفع الحروري غير المفسر و بزل نقي عظم عند عدم الوصول لتشخيص من اللطاخة، كما تم إجراء خزعة عظم و نقي عند الضرورة لاستكمال الدراسة الدموية. ثم تحديد الجدوى التشخيصية لهذه الإجراءات في الحمى مجهولة السبب. النتائج: شملت الدراسة 87 مريضا لديهم حمى مجهولة السبب، تم الوصول إلى تشخيص نوعي عند 67 (77%) مريضاً و كانت الأسباب الإنتانية عند 24 (27%) مريضاً هي الأشيع في هذه الدراسة. بلغت الجدوى التشخيصية للطاخة الدموية المحيطية و بزل نقي العظم نسبة 16% و 31% على التوالي، واعتبرت خزعة العظم والنقي مشخصة عند11 (13%) مريضاً. تم الوصول إلى تشخيص نوعي بدون إجراء الدراسة الدموية عند 15 (17%) مريضاً، و مع إجراء الدراسة الدموية الخلوية زادت النسبة التشخيصية إلى 64%. و أما عند إجراء الدراسة الدموية المتكاملة (الدراسة الخلوية مع خزعة النقي ) ارتفعت القيمة التشخيصية إلى 77%. الخلاصة: إن فحص اللطاخة الدموية المحيطية و نقي العظم أظهر قيمة تشخيصية هامة في تقييم مرضى الحمى مجهولة السبب للوصول إلى تشخيص نوعي أو إلى مفتاح تشخيصي لمرض م